KNPI KOTA PADANG DALAM MENGHADAPI PERUBAHAN SOSIAL ERA ORDE BARU MENUJU REFORMASI - Nora. AN, Desri (Humanus, 2014)
This article reveals the condition of KNPI as an organization that accommodate all youth organizations in facing social change that occurred in Indonesia from the New Order Regime towards Reformation Order. The results of this study shows that during the New Order Regime, KNPI became an extension of the ruling party and this codition is still affecting KNPI in the reformation era although Indonesia has undergone a social change. Keywords: KNPI, social change, reformation.